Sports and exercise nutrition - McArdle, William D. Professor Emeritus; Katch, Frank I.; Katch, Victor L. (Wolters Kluwer, 2019)
"The goal of the text is to illustrate the "integration of nutrition and exercise and its impact on optimal exercise performance and training responsiveness." This is the most in depth and detailed sports nutrition book on the market authored by the well-known team of McArdle, Katch and Katch. The challenge of this course is presenting nutrition content/material at the level that is appropriate for those studying exercise science and not nutrition"--Provided by publisher.